Myocardial fibrosis quantification by cardiac CT predicts outcome in severe aortic stenosis. (8th February 2021) - Scully, P; Patel, KP; Augusto, JB; Klotz, E; Lloyd, G; Kelion, A; Kennon, S; Ozkor, M; Mullen, M; Cavalcante, JL; Menezes, LJ; Hawkins, PN; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Background: Myocardial extracellular volume (ECV) increases with fibrosis, oedema or infiltration. ECV by CMR predicts all-cause and cardiovascular mortality in severe AS after valve intervention. Previous studies have shown that ECV can be reliably quantified by computed tomography (ECVCT), but these studies have not differentiated between ECV elevation due to fibrosis or cardiac amyloid deposition (13-16% of patients with severe AS). Purpose: We hypothesised that ECVCT quantification, performed as part of a transcatheter aortic valve implantation (TAVI) work-up CT, predicts survival in patients with severe AS without cardiac amyloid (lone AS). Methods: Patients aged ≥75, with severe AS, referred for TAVI at Barts Heart Centre (as part of ATTRact-AS (NCT03029026)) underwent CT as part of their clinical work-up. All patients had 99mTc-3, 3-diphosphono-1, 2-propanodicarboxylic acid (DPD) scintigraphy and those with a positive result were excluded. CT was performed on a 128-slice dual-source 3rdgeneration scanner (Siemens Somatom FORCE) and ECVCT was acquired during the TAVI work-up CT using additional pre- and 3-minute post-contrast 'axial shuttle mode' acquisitions (no additional contrast). ECVCT was calculated from the Hounsfield units (HU) and a venous haematocrit (HCT): ECVCT = (1-HCT) x (ΔHUmyo/ΔHUblood). Results: Following exclusion of 16 patients with cardiac uptake on DPD, 93 patients (41% male, aged 85 ± 5 years) were included in the study. All patients had severe AS (AV Vmax 4.12 ± 0.63m/s, mean AV gradient 42 ± 14mmHg, AVA 0.71 ± 0.23cm2). The mean HCT was 0.38 ± 0.04 and total dose-length product for additional research scans was 364 ± 41 mGy.cm. 76 patients (82%) underwent TAVI. ECVCT was 32 ± 3% in the entire cohort, which we then split into those with a 'higher' ECVCT (>34%, n = 23, representing the highest quartile) and those with a 'lower' ECVCT (≤34%, n = 70, representing the lower quartiles). Over a median follow-up of 25 months (IQR 17-34 months) there were 27 deaths (29%), of whom 11 did not undergo TAVI (41%). There were 10 deaths in the 23 patients (44%) with a higher ECVCT, compared to 17 in the 70 patients (24%) with a lower ECVCT (p = 0.03, figure 1). This mortality difference remained significant when those patients who did not undergo TAVI were excluded (p = 0.03). Conclusions: Myocardial fibrosis quantified by ECVCT is associated with a significantly worse prognosis in lone AS, even after patients with AS-amyloid are excluded. ECVCT can be performed as a simple addition to the TAVI work-up CT and provides additional prognostic information.